Modification of PVC and PVC Copolymer by Substitution Imide Groups - AL-Salami, F.M. A.; AL-Duri, A. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this work the poly vinyl imides were prepared as thermal l y stable polymers by modified PVC and PVC copolymers \’lith different cyclic imides such as naphtha imide, phtbal imide, male imide and succin imide as a pendant groups. This method gave new polyimides, from considered especially plastic because of their outstanding high performance properties. As such, they are priced well above commodity polymers such as PVC and PVC copolymers. All the prepared polymers were characterized by IR, UV spectroscopy, elemental analysis and chemical reactions, and thermal analysis such as DTA and TG. Physical properties and the viscosities for all prepared polyimides were determined by using DMF as a solvent. This method gave good results and the new modification of PVC thermoplastic polymer to the PVC-link with different irn i des gave higher the1mally stable polymers compaired with the origin PVC polymer.